Peripheral Ossifying Fibroma: A Case Report: Life Sciences-Periodontitis for Dental health - Dr. Romita Dilip Gaikwad; Dr. Farooque Khan (International Journal of Life Science and Pharma Research, 2022)
The gingiva is often considered as one of the most common sites of localized growths that are considered to be reactive rather than malignant in nature. Clinically, the majority of these lesions are difficult to identify, and therefore histopathology is useful in diagnosing these lesions as specific entities only on the basis of typical and consistent features. Focal gingival enlargements are quite frequent lesions in the oral cavity amounting to almost 3.1% of all oral tumors and 9.6% of gingival lesions. Peripheral ossifying fibroma (POF) is one of the reactive lesions that have typical histopathological features. Since the late 1940s, intraoral ossifying fibromas have been discussed in the literature. The term “Peripheral ossifying fibroma” is usually used to describe a fibroma of the gingiva which shows areas of calcification or ossification. They are usually classified as non-neoplastic enlargement of the gingiva. Many POFs are thought to develop initially as a pyogenic granuloma that undergoes fibrous maturation and subsequent calcification. However, many authors have suggested that rather than a transitional form of pyogenic granuloma or irritation fibroma, POF represents a separate clinical entity. Different lesions with clinical presentations similar to POF make it difficult to arrive at an appropriate diagnosis. Usually, the treatment of POF includes excision of the lesion surgically with minimal chances of recurrence. This paper describes a case report of a 32 year old female patient who reported growth on gingiva in the mandibular left anterior region of the mouth for three years.